Análisis para el desarrollo de un chatbot, para la mejora de los servicios de los usuarios de la dirección del talento humano de la Universidad Técnica de Babahoyo - Urrutia Ortiz, Jhon Alexander (2023)
The document analyzes the need to develop a chatbot to improve the services of the Faculty of Human Talent of the Technical University of Babahoyo. This chatbot could offer a number of advantages, such as providing quick and accurate responses to user queries, automating processes, and ensuring a personalized user experience. Additionally, a series of challenges are identified that must be addressed to develop a successful chatbot, such as identifying specific user needs, choosing the appropriate technological platform, determining the required functionality, integrating with the existing university system, and ensuring an easy-to-use experience. use and custom. Consideration should also be given to the ethical and privacy implications of collecting and processing personal data. It concludes that the use of chatbots has the potential to significantly improve the services of the Faculty of Human Talent of the Technical University of Babahoyo. Chatbots could help the university respond more quickly to user queries, free up staff for more strategic tasks, and provide a more personalized user experience. In particular, the following benefits of using chatbots in human resource management at a university are highlighted and overall, the paper provides a solid assessment of the potential benefits of using chatbots at the Technical University of Babahoyo. Developing a well-designed and executed chatbot could help the university better serve its users and improve the efficiency of its operations.